Competition as a Factor of Social Development - Aleksandrova, Olena; Omelchenko, Yurii; Popovich, Olena (Studia Warmińskie, 2018)
The article is dedicated to the phenomenon of competition. The analysis conducted by the authors is aimed at showing the links between individual factors that make up the phenomenon of competition. The authors also focused on showing the role of competition in the development of society. They distinguished in the analyzed area the following notions: subject of competition, object of competition, competition, competitive environment, social development (progress), individual competitiveness, social systems, material and ideal formations, competitive relations, competitive struggle, types of competition, competition functions. However, the impact of competition on the development of society was noted in the following functions of this phenomenon: regulatory, indirect, controlling, generating, stimulating and protective. In turn, from the point of view of shaping public order in society, several types of competition can be distinguished: cooperating, competing, partnering, conflict and confrontation. The role of competition in society is therefore important, because thanks to this phenomenon, there is a redistribution of limited social resources through which the regulation of socio-economic, political and cultural processes takes place.